Comment on: “Atom‐Modified gDNA Enhances Cleavage Activity of TtAgo Enabling Ultrasensitive Nucleic Acid Testing” - Yue Tang; Xiao‐han Wang; Xu Xu; Lu‐sheng Xin; Xiu‐dan Wang; Xin‐min Li (Advanced Science)
Abstract The recent article by Zhang et al. piqued the interest. An atom‐modification‐based strategy is reported to enhance the cleavage activity of TtAgo, improving its practicability in TtAgo‐based nucleic acid testing. Specifically, the 2′‐fluorine (2′F)‐modified guide DNA (2′F‐gDNA) shows significant enhancement in the cleavage activity of TtAgo on double‐stranded (dsDNA) by increasing the melting temperature (Tm) and strengthening the binding affinity between 2′F‐gDNA and the targeted dsDNA. These findings are considered important for both molecular diagnostics and gene editing. A careful review of the article, however, raises questions that merit further discussion. After comprehensively reviewing the cleavage mechanism and structure of TtAgo‐gDNA‐target ternary complexes, and thoroughly analyzing our results, it is believed that the increased Tm and binding affinity of 2′F‐gDNA are not the primary factors that enhance cleavage activity, it is speculated that the 2′F modification at gDNA 3′‐end likely influences the propagation step. The data suggest that several details need to be addressed to improve the robustness of 2′F‐gDNA/TtAgo cleavage.